2005
DOI: 10.1159/000086197
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Mechanics of the Temporomandibular Joint

Abstract: Direct measurement of temporomandibular joint (TMJ) tissue deformation requires animal experimentation. Most of the available data pertain to the mechanical strain on the bone surfaces around the joint. However, bone is rarely the first joint tissue to show injury, being affected after damage to collagenous tissues such as the disc or capsule. Capsular ligaments guide or limit movement, while the intra-articular disc may also distribute joint loads. However, these tissues are difficult to visualize dynamically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Chondrocytes and FCs both respond to mechanical signals in a magnitudedependent manner. The anti-inflammatory actions of mechanical signals are observed at magnitudes close to those experienced by chondrocytes during normal joint movement (16,17,19,20,34). In this report we have shown for the first time, that at low magnitudes mechanical signals down-regulate activation of TAK1, to intercept intracellular proinflammatory responses generated by several different proinflammatory insults.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Chondrocytes and FCs both respond to mechanical signals in a magnitudedependent manner. The anti-inflammatory actions of mechanical signals are observed at magnitudes close to those experienced by chondrocytes during normal joint movement (16,17,19,20,34). In this report we have shown for the first time, that at low magnitudes mechanical signals down-regulate activation of TAK1, to intercept intracellular proinflammatory responses generated by several different proinflammatory insults.…”
Section: Discussionmentioning
confidence: 53%
“…During joint movement, the disc elongates in antero-posterior axis, and experiences tensile forces around 8% on the balancing side and 16% on the working side (34). We have observed that FCs when exposed to tensile forces at a magnitude of 12% elongation inhibit proinflammatory responses.…”
Section: Discussionmentioning
confidence: 80%
“…These relative positions then switch during the occlusal phase, when the contralateral/BS condyle experiences retraction and the ipsilateral/WS condyle experiences protraction. The differential translations of the contralateral/BS condyle affect soft tissue deformation and strain at the TMJ Sindelar and Herring, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The strongly curved surface of the articular eminence permits anterior movements of the condyle. Posteriorly, the postglenoid wall is absent in pigs and the space is filled with a fibrous-fatty retrodiscal pad, which is flexible enough to allow slight retraction of the mandibular condyle (Sindelar and Herring, 2005). Thus, based on both bony and soft tissue morphology, we anticipate a high degree of anteroposterior mobility for the mandibular condyles in the miniature pig.…”
Section: Introductionmentioning
confidence: 99%
“…• Temporomandibulares (DTMs) têm sido estudadas em suínos (CHEUNG et al, 2007;HERFORD et al, 2005;NAVARRO et al, 2008;NAVARRO et al, 2008;HERRING, 2005;SINDELAR et al, 2003;THURMULLER et al, 2006;THURMULLER et al, 2002;WARD et al, 1990;ZOUHARY;FEINBERG, 2006 cúspides dos dentes inferiores são muito menos importantes, sendo a força da mastigação controlada pela musculatura (HERRING, 1995).…”
Section: Figura 1: Gráfico Ilustrando O Crescimento Do Número De Pesqunclassified